Wireless blood velocity spectra measurement system for healthcare evaluation: reference data - Noor Azmi, Azran Azhim; Akutagawa, Masatake; Yoshizaki, Kazuo; Obara, Shigeru; Nomura, Masaharu; Tanaka, Hiroyuki; Yohsuke , Kinouchi (IEEE, 2008)
The aim of the present study was to determine the blood velocity and its indices in common carotid artery (CCA) as reference value for clinical and healthcare application using the constructed portable wireless Doppler blood flow velocimeter system. Evaluation of CCA blood velocity waveforms was performed in 202 healthy volunteers in the age range of 20 to 69 years. Multivariate analysis was used to determine the relationship between the fixed factor and the outcome hemodynamic variables after adjustment for the related covariates. Results show a general age-related decrease in flow velocities and change in the velocity waveform. There is also a gender difference in velocity indices, except for peak systolic blood velocity. Gender difference is also found in systolic and pulse blood pressures. The findings suggest that waveform indices provide a more reliable evaluation of effects of aging and gender on CCA flow. In conclusion, normal CCA blood velocity parameters are determined in a total of 202 healthy volunteers between the third and seventh age decade after adjustment for gender and exercise effects. Findings may contribute to improved means of healthcare monitoring and clinical evaluation.